Investigation of Using the IL-FSSW Technique to Weld AA5052-H112 Alloy with Copper: Experimental Study - Kareem Abbas Falih; Isam Jabbar Ibrahim; Sabah Khammass Hussein; Salah Mezlini (Journal of Techniques)
In this research, a developed welding technique (IL-FSSW) was used to bond alloys from Aluminum with pure Copper. Aluminium alloy AA5052-H112 and pure copper with an intermediate layer from the same base metal with a thickness of 2mm were used in the present study. The mechanism of achieving spot welding in this process differed from that of the conventional FSSW process in terms of introducing the Intermediate layer (IL) and using a pinless tool to solve the keyhole problem, and get a flat surface for the welding spot, thus increasing the tensile shear strength of the joints which makes it suitable for engineering applications. In addition, the work is based on the use of solid-state welding to eliminate the problems of conventional fusion welding methods, and this reduces the additional operations or subsequent treatments of welding and makes them unnecessary. The work was evaluated by examining the tensile shear strength and analysing the microstructure using light microscopy. The results showed a good joint appearance with shallow keyholes. The failure load value from the shear tensile test was 5008 N, obtained at a Rotating speed of 1400 rpm, feeding 20 mm/min, soaking time 20 sec, and preheating 20 sec, which was higher after comparing with the required strength value by the requirements of the American Welding Society. The microstructure images of the cross-section of the sample showed a change in the size of the crystalline grains between the welded zone and the base metal.